Diálogos entre o Ensino de Artes Visuais no Brasil e em outros contextos - Bastos, Flávia Maria Cunha; Barreto, Umbelina Maria Duarte (Revista GEARTE, 2018)
Diálogos entre o Ensino de Artes Visuais no Brasil e em outros contextos